Phytochemical Screening, Acute Toxicity Study, and Pharmacological Evaluation of Natsiatum herpeticum Buch.Ham. ex Arn. - Hazarika, Sangeeta; Hemalatha, Siva; Venugopala, Katharigatta Narayanaswamy (Indian Journal of Pharmaceutical Education and Research, 2023)
Background: Plants are an open treasure of diverse pharmacologically active scaffolds. Natsiatum herpeticum, a least exploited plant, is known to be consumed by various ethnic groups of Asian origin as edible or as part of traditional remedy. Materials and Methods: The Ethanolic Extract of N. herpeticum (EENH) was evaluated for acute oral toxicity using acute toxic class method (OECD 423). Here, we aimed to investigate the free radical scavenging (antioxidant) and in vitro anti-inflammatory property of the plant extract. Results: Acute toxicity result suggests the plant to be safe and can be categorised under category 5 of GHS classification. The EENH showed promising antioxidant activity in DPPH (IC50 value = 84.1 µg/mL) and ABTS (IC50 value = 81.8 µg/mL) method. Similarly, the plant extract demonstrated good in vitro anti-inflammatory activity (IC50 value = 80.88-93.26 µg/mL). Conclusion: The plant can be considered as safe to be consumed. The plant extract exhibited promising in vitro antioxidant and anti-inflammatory activity, which are further to be tested in in vivo models.
Keywords: Acute toxicity; Antioxidant; Anti-inflammatory; Natsiatum herpeticum